Evolutionary drivers of sexual signal variation in Amazon Slender Anoles. (5th May 2021) - Prates, Ivan; D'Angiolella, Annelise B.; Rodrigues, Miguel T.; Melo‐Sampaio, Paulo R.; de Queiroz, Kevin; Bell, Rayna C.
Abstract: Phenotypic variation among populations, as seen in the signaling traits of many species, provides an opportunity to test whether similar factors generate repeated phenotypic patterns in different parts of a species' range. We investigated whether genetic divergence, abiotic gradients, and sympatry with closely related species explain variation in the dewlap colors of Amazon Slender Anoles, Anolis fuscoauratus . To this aim, we characterized dewlap diversity in the field with respect to population genetic structure and evolutionary relationships, assessed whether dewlap phenotypes are associated with climate or landscape variables, and tested for nonrandom associations in the distributions of A. fuscoauratus phenotypes and sympatric Anolis species. We found that dewlap colors vary among but not within sites in A. fuscoauratus . Regional genetic clusters included multiple phenotypes, while populations with similar dewlaps were often distantly related. Phenotypes did not segregate in environmental space, providing no support for optimized signal transmission at a local scale. Instead, we found a negative association between certain phenotypes and sympatric Anolis species with similar dewlap color attributes, suggesting that interactions with closely related species promoted dewlap divergence among A. fuscoauratus populations. Amazon Slender Anoles emerge as a promising system to address questions about parallel trait evolution and the contribution of signaling traits to speciation.